RANIBIZUMAB FOR DIABETIC MACULAR EDEMA REFRACTORY TO MULTIPLE PRIOR TREATMENTS. Issue 7 (July 2016) - Ciulla, Thomas A.; Hussain, Rehan M.; Ciulla, Lauren M.; Sink, Bethany; Harris, Alon
Abstract : Purpose: Diabetic macular edema can be refractory to multiple treatment modalities. Although there have been anecdotal reports of ranibizumab showing efficacy when other modalities provided limited benefit, little has been published on treatment for refractory diabetic macular edema. This study sought to investigate this observation further. Methods: Retrospective chart review. Results: Thirty-three eyes of 22 patients with refractory diabetic macular edema were treated with 0.3 mg intravitreal ranibizumab. This group of eyes received an average of 5.1 prior treatments (macular laser, intravitreal bevacizumab, triamcinolone acetonide, or dexamethasone implant). The mean best corrected visual acuity before the initial ranibizumab injection was 20/110 and the mean central subfield thickness was 384 μ m. After 7 visits over an average of 48 weeks, during which an average of 6 ranibizumab injections were administered, the mean visual acuity improved to 20/90 and the mean central subfield thickness improved to 335 μ m. Both central subfield thickness and best corrected visual acuity improved with number of days of follow-up in a statistically significant fashion ( P < 0.01). Similarly, both central subfield thickness and visual acuity improved with number of ranibizumab injections in a linear fashion, but this was not statistically significant. Conclusion: Ranibizumab can improve diabetic macular edema refractory to prior treatments of laser photocoagulation, intravitreal triamcinolone acetonide, and bevacizumab. Abstract : The authors reviewed 31 eyes of 22 patients with refractory diabetic macular edema, treated with an average of six 0.3 mg intravitreal ranibizumab injections over 48 weeks. Mean visual acuity and central subfield thickness showed statistically significant linear trends in improvement with respect to days of follow-up.